ChemInform Abstract: Cinchona Alkaloids as Organocatalysts in Enantioselective Halofunctionalization of Alkenes and Alkynes. Issue 28 (15th July 2014) - Zheng, Suqing; Schienebeck, Casi M.; Zhang, Wei; Wang, Hao‐Yuan; Tang, Weiping
Abstract Review: [72 refs.